Evolution of mechanical properties of concrete with temperature and humidity at high temperatures. (August 2018) - Kallel, Hatem; Carré, Hélène; Laborderie, Christian; Masson, Benoit; Cuong Tran, Nhu
Abstract: The mechanical behavior of concrete in tension is studied at different values of water saturation for temperatures ranging from 110 °C to 160 °C. In order to prevent the concrete from drying, the experiments are performed at the vapor saturation pressure in a specific vessel. Inverse analysis based on numerical simulation is used to compute the values of fracture energy, tension strength and elasticity modulus. The experimental results show that the fracture energy is increasing with saturation and temperature, while the tension strength and the modulus of elasticity are decreasing for a saturation ranging from 35% to 65% and then increasing for higher values of saturation, while they decrease slightly with temperature.